Development of a training program in simple bookkeeping and Microsoft Excel for Hawkers and MSMEs in TBM Sakila Kerti Tegal - Yuannisa Aisanafi (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
As the most significant contributor to the Indonesian economy, MSMEs, which are Micro, Small, and Medium-sized Enterprises, play an essential role in reducing unemployment as they are resilient and resistant to economic crises. So, developing their activities or business and paying attention to the financial reports is crucial. The hawkers and traders in MSMEs also urgently need to be facilitated and assisted in financial literacy, starting from the simple bookkeeping process. This development of the assistance program is intended to provide materials and assistance to traders or hawkers and MSMEs in Taman Baca Masyarakat Sakila Kerti Tegal, particularly in the bus station area. By giving presentations, discussions, and case studies, followed by direct assistance, it is proven that the level of understanding and ability to do simple bookkeeping processes has increased and resulted in better knowledge and literacy. Moreover, Microsoft Excel has been introduced as a helpful software for MSMEs in the bookkeeping process, which increases their awareness of utilizing the usefulness of information technology. AbtsrakSebagai kontributor terbesar atas ekonomi Indonesia, Usaha Mikro Kecil dan Menengah (UMKM) berperan signifikan dalam mengurangi pengangguran karena kemampuannya bertahan pada krisis ekonomi. Sehingga, penting bagi mereka untuk bisa membangun bisnisnya dengan baik dan memberi perhatian lebih pada proses pencatatan akuntansi. Para pedagang asongan dan pedagang yang juga termasuk dalam UMKM juga sangat perlu difasilitasi dan dibantu dalam hal literasi keuangan, dimulai dari pembukuan sederhana. Pengembangan program pelatihan ini bertujuan untuk memberikan pendampingan berupa materi dan pelatihan langsung kepada para pedagang asongan dan UMKM di Taman Baca Masyarakat Sakila Kerti Tegal, khususnya di kawasan terminal bus. Dengan memberikan presentasi, diskusi, dan studi kasus yang dilanjutkan dengan pendampingan langsung, terbukti bahwa tingkat pemahaman dan kemampuan melakukan pembukuan sederhana semakin meningkat dan menghasilkan pengetahuan dan literasi yang lebih baik. Selain itu, pengenalan Microsoft Excel sebagai perangkat lunak yang berguna bagi UMKM dalam melakukan proses pembukuan juga telah dilakukan untuk meningkatkan kesadaran mereka dalam memanfaatkan kegunaan teknologi informasi.Kata Kunci: Akuntansi; pembukuan; UMKM